Persepsi Pesantren terhadap Non-muslim dalam Kitab Fiqh Klasik (Studi Kasus di Provinsi Gorontalo) - Nova Effenty Muhammad (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Institut Agama Islam Negeri Sultan Amai Gorontalo, 2021)
This study concentrates on the views of pesantren residents towards non-Muslims. According to the kitab kuning (yellow book) studied by Islamic boarding schools, non-Muslims are categorized in the second position in life. In this study, we found that although non-Muslims are the second category in the yellow book from the opinion of the ulama, pesantren residents who have experience living with non-Muslims can still give an equal level. Specifically from this research, the formulation of the problem is how is the perception of pesantren towards non-Muslims? and is the pesantren's religious view of non-Muslims influenced by the yellow book? To analyze the perception of pesantren towards non-Muslims, we use qualitative analysis with three approaches: normative, sociological, and cultural. We used the collective data method with observations, interviews, and documents. This study argues that although non-Muslims are the second category in the yellow book but when the teacher has new knowledge, he will interpret it, trying to interpret the yellow book that is friendly because they have the reality of living with non-Muslims. Pesantrens that have experience living with non-Muslims tend to be inclusive, while pesantrens that do not have experience of living with non-Muslims tend to be exclusive.